Network effects in C-ITS – an analysis approach based on conditional probability and system characteristics - Risto Öörni (European Transport Research Review)
Abstract The paper presents an approach for analysing network effects in cooperative intelligent transport systems (C-ITS). The approach is based on the conditional probability of an already-equipped user receiving a warning or other required information, and a framework is provided for analysing the conditional probability of a successful exchange of information. The approach and the framework are validated by applying them to the road hazard warning use case of C-ITS implemented with vehicle-to-vehicle (V2V) communication. The results suggest that even relatively low fleet penetrations may allow communicating a road hazard warning as a decentralized environmental notification message (DENM), with a high probability of success, when the hazard is detected and the related DENM transmitted by an oncoming vehicle travelling in the opposite direction to the user’s vehicle on a single-carriageway interurban road. The approach used in the paper and the analysis results for the road hazard warning contribute to the understanding of network effects in C-ITS use cases and their relationship to the operational context of C-ITS systems, such as parameters related to traffic flow.